Cell growth effect of perivitelline fluid from horseshoe crab on stem cells from human exfoliated deciduous teeth - Ibrahim, Najian (2018)
Perivitelline fluid (PVF) from the fertilized eggs of a horseshoe crab has been reported to support embryogenesis, enhance cell growth and differentiation as well as promote organ regeneration in certain organisms. The effect of PVF (0.019 mg/ml) on stem cells from human exfoliated deciduous teeth (SHED) were investigated with regard to cell viability using LIVE/DEAD viability/cytotoxicity kit for mammalian cells. The cell viability in PVF treated SHED and control group (SHED without PVF treatment) were assessed by observing the live and dead cells using fluorescence microscope and the percentage of live and dead cells using fluorescence microplate reader for 3 consecutive day(s), 1, 2 and 3. The results showed that the viability of SHED was as demonstrated by the higher live cell percentage in the PVF treated group compared to control. The percentage of live cells in PVF treated group remained higher than 90% for 3 days while in the control group, the live cell percentage dropped to 76.09% on the third day of test. Moreover, the fluorescence microscopy images also demonstrated more live and viable SHED in the PVF treated group until day 3 compared to the control which showed the presence of dead (red) cells. The expression of selected cell cycle regulatory genes in control and PVF treated SHED were compared using reverse transcriptase polymerase chain reaction (RT-PCR) on day(s) 1, 3, 7, 14 and 21. Mann-Whitney test was used to determine the significant difference in the gene expression between both groups of SHED. Cell cycle regulatory genes,CDKN2A, PTEN and TP53 expressed significantly higher in the PVF treated group compared to control (p ≤ 0.05) on day 7 until day 21 which proposes that PVF treatment enhances SHED growth and proliferation. On the contrary, the expression of MDM2, an oncogene, remained at low levels in the treated group throughout the whole experiment indicating that PVF did not result in cell cycle arrest in SHED. Faint and low expression of apoptotic activator gene, BCL2L11 was observed in the PVF treated group from day 1 until 14 with a sudden peak on day 21, demonstrating that overcrowding of SHED in the confined culture flask could have induced the expression of BCL2L11 which activates cell death signalling pathways towards the 21st day of incubation. Hence, it can be concluded that PVF plays a role in cell cycle regulation, proliferation and growth and increases the viability of SHED.